Sn-imidazolates supported on boron and nitrogen-doped activated carbon as novel catalysts for acetylene hydrochlorination. Issue 9 (1st September 2020) - Wu, Yibo; Li, Fuxiang; Xue, Jianwei; Lv, Zhiping
Abstract: This study mainly reports on the preparation of Sn-imidazolates (Sn(Im) n ) supported on boron and nitrogen-doped activated carbon (AC), which proved to be highly active catalysts for the acetylene hydrochlorination. The obtained materials were characterized by FTIR spectroscopy, X-ray diffraction, N2 physisorption, scanning electron microscopy, thermogravimetry, temperature programed desorption, and X-ray photoelectron spectroscopy. The catalytic results revealed that the Sn(Im) n /AC materials manifest enhanced activity and long-term stability than SnCl2 /AC catalyst. Regarding the lifetime, 10%Sn(Im) n /(10%BNAC-800) catalyst, exhibiting an acetylene conversion of 80% after 40 h of reaction, is more promising in comparison with 10%Sn(Im) n /AC. These results indicate that the use of 2-methylimidazole improve the activity and stability of SnCl2 /AC catalysts in the hydrochlorination of acetylene. Particularly, the supports modified with boric acid and melamine can effectively increase the lifetime of Sn(Im) n /AC catalysts.